2009
DOI: 10.1107/s1600536809020145
|View full text |Cite
|
Sign up to set email alerts
|

(E)-3-(2,6-Dichlorophenyl)-1-(4-methoxyphenyl)prop-2-en-1-one

Abstract: In the title compound, C16H12Cl2O2, the dichloro­phenyl and methoxy­phenyl groups are linked by a prop-2-en-1-one group. The C=C double bond is trans configured. The mol­ecule is not planar, as can be seen from the dihedral angle of 6.21 (7)° between the planes of the two rings. The crystal structure can be described by two types of crossed layers which are parallel to (110) and (10).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For general background to chalcones and their biological properties, see: Choudary et al (1999); Tomazela et al (2000). For a related structure, see: Benmekhbi et al (2009). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For general background to chalcones and their biological properties, see: Choudary et al (1999); Tomazela et al (2000). For a related structure, see: Benmekhbi et al (2009). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…The other methoxy group at O2 is in a + synclinal conformation as indicated by the torsion angle 73.6 (2)° for C14-O2-C13-C12. The C═C double bond exhibits an E conformation (Benmekhbi, et al, 2009). The crystal structure is stabilized by two different C-H•••O intermolecular interactions generating chains of molecules along the b-axis (Fig.…”
Section: S1 Commentmentioning
confidence: 99%
“…Compounds 4‐(phenyldiazenyl)‐1 H ‐pyrazole‐3,5‐diamine derivatives, [17] 2‐cyanoacetohydrazide, [18] 1,3‐diphenyl‐1 H ‐pyrazole‐5‐carbaldehydes, [19] ethoxymethylenemalononitrile, [17,20] bis (methylthio)‐methy‐lenemalononitrile, [21] 2‐(phenyldiazenyl)malononitrileanalogues, [22,23] and 3‐(2,4‐dichlorophenyl)‐1‐(aryl)prop‐2‐en‐1‐one derivatives [24,25] were prepared according to the reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Anticancer research was conducted on local strain found in the Regional Center for Genetic Engineering, Faculty of Science (Boys), University of Al-Azhar, and the findings were within ±0.4% of the measured outcome. Compounds 4-(phenyldiazenyl)-1H-pyrazole-3,5-diamine derivatives, [17] 2-cyanoacetohydrazide, [18] 1,3-diphenyl-1Hpyrazole-5-carbaldehydes, [19] ethoxymethylenemalononitrile, [17,20] bis(methylthio)-methy-lenemalononitrile, [21] 2-(phenyldiazenyl)malononitrileanalogues, [22,23] and 3-(2,4dichlorophenyl)-1-(aryl)prop-2-en-1-one derivatives [24,25] were prepared according to the reported procedures. were heated under reflux in dioxane/DMF mixture (10/5 mL), containing few drops of TEA for 13 hours.…”
Section: Chemistrymentioning
confidence: 99%
“…For general background to chalcones, see: Tomazela et al (2000); Uchida et al (1998); Zyss & Chemla (1987). For related structures, see: Benmekhbi et al (2009). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%